Bis(silylene)-Stabilized Monovalent Nitrogen Complexes - Yao, Shenglai; Szilvási, Tibor; Xiong, Yun; Lorent, Christian; Ruzicka, Ales; Driess, Matthias (Angewandte Chemie (International ed. in English), 2020)
The first series of bis(silylene)-stabilized nitrogen(I) compounds is described. Starting from the 1,2-bis(N-heterocyclic silylenyl) 1,2-dicarba-closo-dedocaborane(12) scaffold 1, [1,2-(LSi)2 C2 B10 H10 ; L=PhC(Nt Bu)2 ], reaction with adamantyl azide (AdN3 ) affords the terminal N-μ2 -bridged zwitterionic carborane-1,2-bis(silylium) AdN3 adduct 2 with an open-cage dianionic nido-C2 B10 cluster core. Remarkably, upon one-electron reduction of 2 with C8 K and liberation of N2 and adamantane, the two silylene subunits are regenerated to furnish the isolable bis(silylene)-stabilized NI complex as an anion of 3 with the nido-C2 B10 cluster cage. On the other hand, one-electron oxidation of 2 with silver(I) yields the monocationic bis(silylene) NI complex 4 with the closo-C2 B10 cluster core. Moreover, the corresponding neutral NI radical complex 5 results from single-electron transfer from 3 to 4.
Keywords: carboranes; redox non-innocent ligands; nitrogen complexes; silylenes; azides